Electromyographic and Kinematic Analysis of the Flexion-Rotation Trunk Test - García-Vaquero, María P; Ruiz-Pérez, Iñaki; Barbado, David; Vera-Garcia, Francisco J (Journal of strength and conditioning research, 2020)
García-Vaquero, MP, Ruiz-Pérez, I, Barbado, D, and Vera-Garcia, FJ. Electromyographic and kinematic analysis of the flexion-rotation trunk test. J Strength Cond Res 34(12): 3386-3394, 2020-Although most trunk endurance field protocols are performed in the sagittal or frontal planes, the flexion-rotation trunk (FRT) test combines trunk flexion with rotation, which may be relevant to rotation-related sports. The aim of this study was to describe the trunk and hip muscle activation and fatigue and the range of hip flexion of this test. Twenty-seven physically active males and females performed the FRT test after a period of practice. Electromyographic (EMG) signals were bilaterally collected from the rectus abdominis (RA), internal oblique (IO), and rectus femoris (RF), and hip flexion amplitude was measured using a biaxial electrogoniometer. Because the fast Fourier transform algorithm requires stationary EMG signals, subjects performed a 6-second isometric trunk flexion-rotation repetition just before and just after the test execution (preexecution and postexecution repetitions, respectively). Rectus abdominis showed the highest mean activation levels (approximately 30% maximal voluntary isometric contractions [MVC]) in the preexecution repetition, followed by IO (approximately 20% MVC). Also, the mean power frequency (MPF) significantly decreased from the pre-execution to the postexecution repetition for RA and IO, which shows abdominal muscle fatigue. Although each trunk flexion-rotation repetition involved an average 8-14° hip flexion, the RF activation was lower than 10% MVC, and no significant MPF reduction (i.e., no muscle fatigue) was observed for this muscle. In addition, significant negative correlations were found between the FRT test scores and the normalized EMG amplitudes of RF. Based on these results, the FRT test seems a valid field protocol to assess abdominal muscle endurance in trunk flexion-rotation exertions.